노인의 정신건강과 주관적 구강건강상태가 치주질환에 미치는 영향 - 김예황; Ye-hwang Kim; 이정화; Jung-hwa Lee (Han'guk Ch'iwisaeng Hakhoe chi, 2019)
Objectives: The purpose of this study was to investigate how mental health status affects oral health in the elderly. Methods: The subjects of the study provided the data for the sixth Korea National Health and Nutrition Examination Survey from 2013 to 2015. Four-hundred and twenty-one subjects were selected for the study. All data were analyzed by complex sampling frequency, chi-square test, and composite multiple regression analysis using SPSS 21.0 version. In addition, a significance level of 0.05 was considered. Results: The general factors affecting cases of periodontal disease were general characteristics, mental health status, oral health status, elderly males, household income, education level, daily brushing frequency, speaking, and stress. The effect of periodontal disease was 1.64 times higher in the male group than in the female group (p<0.001). In the household income level, the ‘low’ group had 1.91 times more periodontal disease, while the ‘mid low’ group had 1.64 times more periodontal disease than the ‘high’ group (p<0.05). Periodontal disease was found to be lower in the group that recognized subjective oral health status as ‘good’ (p<0.05). The study subjects had low levels of periodontal disease when there was no speaking difficulty (p<0.05). Conclusions: Therefore, in order to improve oral health of the elderly, it is necessary to understand the mental health condition of the elderly and prepare proper oral health education programs accordingly. Institutional devices for various oral health projects should be prepared, as well.